DEVELOPMENT OF UKRAINIAN TERRITORIES WITHIN THE FRAMEWORK OF PARTNERSHIP WITH THE EUROPEAN UNION - V.S. Shebanin; I.V. Kormyshkina (Aktualʹnì Problemi Rozvitku Ekonomìki Regìonu)
The article focuses on the prospects for the development of Ukraine's territories within the framework of partnership with the European Union (EU). The relevance of the research is determined by current challenges such as full-scale war, economic crises, and social instability, which necessitate a new approach to regional governance. The aim of the article is to analyze the interaction between Ukraine and the EU in the context of regional development and assess the impact of European integration processes on the socio-economic state of Ukrainian territories.